The Role Of Management Development Programs In Developing Knowledge And Skills Of Managers In Telekom Malaysia - Abd Rahman, Makmor (2001)
The study was conducted among 175 senior executives and managers using a selfreported questionnaire covering various important aspects of MDps. The study examines factors such as providers, types, contribution and effectiveness of off-the-job and on-the-j